A Randomized Controlled Trial of Sequential Pegylated Interferon-α and Telbivudine or Vice Versa for 48 Weeks in Hepatitis B E Antigen-Negative Chronic Hepatitis B. Issue 1 (January 2013) - Piccolo, Paola; Lenci, Ilaria; di Paolo, Daniele; Demelia, Luigi; Sorbello, Orazio; Nosotti, Lorenzo; Angelico, Mario
Background: Short-term treatment for hepatitis B e antigen (HBeAg)-negative chronic hepatitis B remains unsatisfactory. The aim of our study was to compare the efficacy and safety of two sequential regimens of pegylated interferon (PEG-IFN)-α and telbivudine (LdT). Methods: Adult patients with biopsy-proven HBeAg-negative chronic hepatitis B, elevated alanine aminotransferase (ALT) and serum HBV DNA≥2, 000 IU/ml were randomized 1:1 at baseline to receive PEG-IFN 180 μg/week for 24 weeks followed by LdT 600 mg/day for 24 weeks (PEG-IFN first), or vice versa (LdT first), plus 24-week follow-up; individuals with HCV, HDV or HIV coinfections and lamivudine resistance were excluded. Primary end points were serum HBV DNA<2, 000 IU/ml and normal ALT at week 72. Results: A total of 30 patients (86% male, median age 48 years) were enrolled: mean ±sd baseline serum HBV DNA was 5.56 ±1.4 log IU/ml and ALT was 2.9 ±2.5x upper limit of normal. At end of follow-up (week 72), HBV DNA<2, 000 IU/ml was achieved in 13.3% of participants in the PEG-IFN first group versus 46.7% of those in the LdT first group ( P =0.046). Mean ±sd ALT levels were significantly lower in the LdT first group (1.3 ±0.9 versus 3.2 ±2.7x upper limit of normal; P =0.03). PEG-IFN dose was reduced in 2 (7%) patients and 1 (7%) patient dropped out due to myalgia. Conclusions: Sequential treatment with 24 weeks PEG-IFN followed or preceded by 24 weeks of LdT is safe. Virological response rate at week 72 was significantly higher in patients treated with LdT followed by PEG-IFN than vice versa. A sequential antiviral regimen of LdT followed by PEG-IFN, if confirmed in larger series, could improve response rates compared with standard PEG-IFN monotherapy.